THE EFFECTIVENESS SURYANAMASKAR YOGA ON ANXIETY IN PREGNANT WOMEN DURING THE COVID-19 PANDEMIC - Nevy Norma Renityas; Dyah Mubarokah A; Wening Pangesthi Maharani (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Widespread anxiety and stress during the pandemic significantly impacted pregnant women, with research indicating a surge in anxiety levels of over 50.67% due to concerns regarding maternal health and postnatal care. To address this, a study evaluated the efficacy of Suryanamaskar yoga in mitigating these psychological pressures. Unlike traditional methods, this research leveraged digital interventions by utilizing Google Meet and instructional videos to facilitate sessions for 20 pregnant woman respondents selected through consecutive sampling. The study employed the Depression Anxiety Stress Scale (DASS) to measure psychological shifts, analyzed via a paired sample t-test with a significance level of 0.05. Initial assessments revealed that 11 respondents experienced moderate anxiety, while nine reported mild symptoms. Following the Suryanamaskar yoga intervention, the results demonstrated a marked improvement: 13 respondents transitioned to normal anxiety levels, and seven remained at a mild level. Statistically, the intervention yielded an average anxiety reduction of 10.8 points. The resulting p-value (ρ < α) confirmed a significant difference in anxiety levels before and after the treatment. These findings suggest that Suryanamaskar yoga serves as an effective midwifery therapy to complement routine clinical check-ups. By integrating this practice into prenatal care, healthcare providers can better support the mental and spiritual readiness of pregnant women. Reducing psychological distress not only enhances maternal well-being but also ensures women are better prepared for the complexities of childbirth and newborn care.